Antitumor action of the peroxisome proliferator-activated receptor-γ agonist rosiglitazone in hepatocellular carcinoma - BO, QI-FU (Oncol Lett, 2015)
The inhibition of apoptosis in cancer cells is the major pathological feature of hepatic carcinoma. Rosiglitazone (RGZ), a ligand for peroxisome proliferator-activated receptor γ (PPAR-γ), has been shown to induce apoptosis in hepatic carcinoma cells. However, the mechanism underlying this effect remains to be elucidated. The present study aimed to investigate the effect of RGZ on cell viability and apoptosis, and its mechanisms in cultured HepG2 cells using MTT assay, flow cytometry and western blotting. The results revealed that treatment with RGZ may attenuate HepG2 cell viability and induce the apoptosis of the cells. The mechanism of RGZ-induced apoptosis involves an increase in the level of activated PPAR-γ (p-PPAR-γ) and a decrease in p85 and Akt expression. In addition, the PPAR-γ antagonist GW9662 suppressed the effect of RGZ in the HepG2 cells. Taken together, the results suggest that RGZ induces the apoptosis of HepG2 cells through the activation of PPAR-γ, suppressing the activation of the PI3K/Akt signaling pathway. Such mechanisms may contribute to the favorable effects of treatment using RGZ in HepG2 cells.